MicroRNA expression profile in primary lung cancer cells lines obtained by endobronchial ultrasound transbronchial needle aspiration - Guarize, Juliana; Bianchi, Fabrizio; Marino, Elena; Belloni, Elena; Vecchi, Manuela; Donghi, Stefano; Lo Iacono, Giorgio; Casadio, Chiara; Cuttano, Roberto; Barberis, Massimo; Di Fiore, Pier Paolo; Petrella, Francesco; et al. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Novel cancer biomarkers like microRNA (miRNA) are promising tools to gain a better understanding of lung cancer pathology and yield important information to guide therapy. In recent years, new less invasive methods for the diagnosis and staging of NSCLC have become key tools in thoracic oncology and the worldwide spread of endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA). However, appropriate specimen handling is mandatory to achieve adequate results and reproducibility. The aim of this single centre prospective study was to evaluate the feasibility of a complete miRNA expression profile in fresh NSCLC cell lines obtained by EBUS-TBNA. Methods: Patients with proven NSCLC underwent EBUS-TBNA for the diagnosis of suspect lymph node metastasis, and cytological specimens were collected for epithelial cell culture and miRNA expression analysis. To validate the miRNA expression profile, we compared the results from EBUS-TBNA NSCLC specimens with those obtained from formalin-fixed paraffin-embedded (FFPE) mediastinoscopy specimens. Results: Analysis of the miRNA expression profiles of three independent EBUS-TBNA-derived primary cell lines allowed the screening of 377 different human miRNAs. One hundred and fifty miRNAs were detected in all cell lines. Analysis of the miRNA expression profile in mediastinoscopy specimens showed a strong similarity in the clusters analysed. Conclusions: The miRNA expression profile is feasible and reliable in EBUS-TBNA specimens. Validation of this protocol in fresh cytological specimens represents an effective and reproducible method to correlate translational and clinical research.